EXPLORING TERTIARY LEARNERS’ PERCEPTION TOWARDS THE USE OF GAMIFICATION IN LEARNING - Kim Lian, Lee; Christopher Luke, Felix (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
To understand the major stakeholders identified as tertiary students on the use of gamification in learning while pursuing their higher education study. A quantitative, descriptive research design of 152 undergraduate students from a private university in Malaysia, taking degree programmes from different various disciplines was conducted to obtain details about their experiences in gamification as a learning tool either inside or outside classroom. In addition, an analysis of their responses on their expectation of gamification in education, attitudes toward gamification and knowledge towards gamification too. Undergraduate students have a positive attitude towards gamification and they believe that its use of learning in classroom is able to generate their interest in learning. The significant of this study is gamification using the game elements have an incredible power in creating long-term engagement of the user experience and such experience and engagement can be translated into anything meaningful learning in higher education, gamification may not only simply play as a form of entertainment, but it can allow user to possess the ability to engage in higher learning.